Conversational Implicature In Indonesian President Candidates Debate on Metro Tv - Asridayani Asridayani; Soekarno Soekarno (Fakultas Sastra Universitas Ekasakti, 2019)
The purpose of this research is to identify kinds and meaning of conversational implicature, especially in President Candidates’ utterances based on context that used in the Indonesian President Candidates Debate on June 2014 in METROTV Television. The data is obtained by identifying the utterances that have implicature, in videos form that have been recorded via mobile phone and downloaded from social media site, it means to make easy in identifying. Then, the identified data are transcribed and analyzed by using Yule’s theory and some books that related and supported the theory. Next, the data analysis is presented by using informal method. The result of the analysis shows that President Candidates’ utterances in the debate contain two kinds on conversational implicature. They are, particularized conversational implicature, it is an implicature that can be assumed by knowing the specific context and also needs special knowledge of the listener. Then, generalized conversational implicature, it is an implicature that does not need context to assume the utterance.